Odpowiedzi

Najlepsza Odpowiedź!
2010-01-12T19:58:00+01:00
2 HNO3 + Ca --> Ca(NO3)2 + H2

Ca(OH)2 + 2HNO3--> Ca(NO3)2 + 2H2O

CaO + 2HNO3--> Ca(NO3)2 + H2O

Ca(OH)2 + N2O5 --> Ca(NO3)2 + H2O

CaO+N2O5 --> Ca(NO3)2

Ca(OH)2 + Mg(NO3)2 --> Ca(NO3)2 + Mg(OH)2

CaSO4 + 2HNO3 --> Ca(NO3)2 + H2SO4

reakcje można przeprowadzić z każdą solą azotową (V)
10 4 10
2010-01-12T20:17:29+01:00
Ca + 2 HNO3 --> Ca(NO3)2 + H2^
CaO + 2 HNO3 --> Ca(NO3)2 + H2O
Ca(OH)2 + 2 HNO3 --> Ca(NO3)2 + 2 H2O
Ca(OH)2 + N2O5 --> Ca(NO3)2 + H2O
CaO + N2O5 --> Ca(NO3)2
6 4 6